Selected Poems of Gregory of Nazianzus I.2.17; II.1.10, 19, 32: A Critical Edition with Introduction and Commentary - Simelidis, Christos (Hypomnemata, 2010)
St. Gregory of Nazianzus' (ca. AD 330-390) classicizing Christian verse is the earliest Greek verse of its kind that survives in any great quantity. This is a critical edition, with introduction and commentary, of four poems (I.2.17; II.1.10, 19, 32). The commentary is primarily linguistic, but attention is paid to historical and theological matters. The poems' fate in Byzantium is also examined and three Byzantine paraphrases are edited in an appendix. The introduction examines features of Gregory's poetry in general. Gregory was an enthusiastic reader of Callimachus and his use of poetic allusion deserves special attention.